A Route to Modernism - Sumner, R. author. aut Link
XIV, 208 p.
Keywords: The question 'What is modernism?' has provoked intense critical discussion. A Route to Modernism explores this area; it focuses on the strange and dangerous journey taken by Hardy, Lawrence and Woolf towards unknown regions of the mind and the universe. In a discussion of these novelists, both individually and in relation to one another, a radical reconsideration of modernism is developed. Woolf envisaged her contemporaries 'flashing past on another railway line'. A Route to Modernism shows the hypothetical train of Hardy, Lawrence and Woolf not following an existing track but tunnelling beneath surfaces, following routes which are 'spasmodic, fragmentary', sometimes taking off like a rocket into the cosmos. Their fragmented, modernist works deny us 'the comfort of ... a single meaning, either in works of art or in the world'. This book offers new approaches to modernism, while insisting on books being left 'open - no conclusion come to '.